FOREIGN EXPERIENCE IN INVESTMENT MANAGEMENT IN CONSTRUCTION ENTERPRISES AND WAYS OF ITS APPLICATION IN OUR COUNTRY (Intent Research Scientific Journal, 2025)
This article analyzes the effective investment management practices in construction companies of developed countries such as the USA, Germany, and Japan. Foreign experience highlights the importance of project selection, risk management, efficiency evaluation, and the use of information technologies. Based on this analysis, the paper proposes priority directions and practical recommendations for applying international investment management practices in Uzbekistan’s construction sector.